Analysis Of Translation Techniques Used in the Translation of Syarah Diwan Imam Asy-Syafi’i by Muhammad Ibrahim Salim - Dinan El Haq Rahimahullah; Akbar Pilayati; Akmaliyah Akmaliyah (Al-Kalimat: Journal of Linguistic and Arabic Teaching, 2025)
The aim of this study is to identify the translation techniques used in the book Syarah Diwan Imam Asy-Syafi’i by Muhammad Ibrahim Salim and to describe how these translation techniques are realized in the translated text. This study employs a qualitative approach with a descriptive research design. In the data collection stage, the researcher applied a library research technique by using Syarah Diwan Imam al-Shafi‘i by Muhammad Ibrahim Salim as the primary data source, focusing on the poem themed “Anjuran untuk Merantau” (Encouragement to Travel), which consists of seven stanzas. The data were classified based on the translation techniques proposed by Molina and Albir. The data analysis process followed the Miles and Huberman model, which consists of four main steps: (1) data collection, (2) data reduction, (3) data display, and (4) conclusion drawing. The results of the study indicate that from the seven stanzas of the poem on encouragement to travel, 63 data items were identified. After being classified according to Molina and Albir’s translation techniques, only 10 out of the 18 techniques were found to be used, namely: (1) literal translation with 12 data, (2) transposition with 1 datum, (3) modulation with 12 data, (4) adaptation with 4 data, (5) established equivalence with 5 data, (6) particularization with 3 data, (7) reduction with 15 data, (8) substitution with 3 data, (9) amplification with 5 data, and (10) linguistic amplification with 5 data.